Intercepción y captación de afluentes al río Cutuchi para la prevención de su contaminación. - Coello Tapia, Luis Alejandro (2020)
The purpose of this research was to determine interception and capture methods of Cutuchi River affluents to prevent contamination and develop channels system that are starting point for the conduction of the fluid and allow quality water to be used on productive activities in at Cotopaxi province, so it has been determined the flow of ten starting points at coordinates (767186.5 - 9919392.9) swampy areas of San Agustín de Callo in Lasso (766228.1 - 9917245.1) by flotation method and current meter method giving a total of 0.79 m3 / s of water that is discharged into contaminated water area, being an unnecessary waste, since this water is coming from water eyes and natural springs and could be used for agricultural, domestic, industrial or human consumption. In this way, the design of the channel in type (trapezoidal) and material (smooth concrete) was established, through the HCanales software that allowed to obtain maximum efficiency of the channel and construction costs of the project were determined with a total value of $ 145,033.90, for water recovery, which has a discharge to Cutuchi river, increasing the volume of contaminated water at central region of the country.